EFEKTIFITAS PELATIHAN TERHADAP KINERJA AGEN PADA DIVISI EKSEKUTIF ASURANSI JIWA BERSAMA (AJB) BUMI PUTERA 1912 BANDUNG - IMAS ROSITAWATI IMAS ROSITAWATI (EKBIS (Ekonomi & Bisnis), 2019)
The aim of reseach are 1). To analyze as far as knowledge about insurance, attitude to confront client, skill to selling polis and effectiveness trainning in knowlarge dimention, attitude, skill as simultaneous effect to agency performance. This research serve quantitative approach and data gathering technique is questioner with the data analysis used path analysis. The result of this research is there’s no significance affect of the knowlarge of insurance products toward improvement of agent performance. On the contrary, there is significance affect on the agent attitude in communicating with client and the skill in selling insurance product toward improvement of agent performance. This conditions lead to the new diagram which eliminated the knowladge of insurance product variabels. The other variabel which would have been affecting the agent performance is social economic of agent. The summary which can be explained is the agent trainning stay at ineffective condition, and still needs improvement especially in knowledge aspect. The recomendation to the management trainee are (1) To improve quality of knowlarge aspect of the agent by training (2)To carry out monthly discussion among agencies about the development of product to improve product knowlarge of agent (3) Agent should be a professional workers which a full responsibility in graining a number of target.